Hierarchically porous N-doped carbon derived from supramolecular assembled polypyrrole as a high performance supercapacitor electrode material. Issue 33 (22nd May 2018) - Lai, Li; Zhao, Yu; Ying, Shu; Li, Lanlan; Ma, Zhong; Pan, Lijia
Abstract : Hierarchically porous N-doped carbon with optimized morphology exhibits an enhanced specific capacitance of 435.6 F g −1 at 0.5 A g −1 and 96.1% capacitance retention after 5000 cycles in 1 M H2 SO4 . Abstract : Rationally designed precursors of N-doped carbon are crucial for high performance carbon materials of supercapacitor electrodes. Herein, we report a scalable preparation of hierarchically structured N-doped carbon of micro/meso porous nanofiber morphology by using a supramolecular assembled polypyrrole as the precursor. The influences of the dose of supramolecular dopant on final products after carbonization and sequential chemical activation were investigated. The interconnected nanofiber backbone allows better electron transport and the optimized hierarchically porous structure of the material exhibits a large specific surface area of 2113.2 m 2 g −1 . The N content of the carbon is as high as 6.49 atom%, which is favorable to improve the supercapacitive performance via additional reversible redox reaction over pure carbon. The hierarchically porous N-doped carbon electrode delivered an outstanding specific capacitance of 435.6 F g −1 at 0.5 A g −1, significantly higher than that of the control sample derived from undoped polypyrrole samples. Moreover, the capacitance retention is as high as 96.1% after 5000 cycles. This precursor's structural control route is readily applicable to various conducting polymers, and provides a methodology to design carbon materials with advanced structure for developing high-performance supercapacitor electrode materials.